2018
DOI: 10.1136/neurintsurg-2017-013092.rep
|View full text |Cite
|
Sign up to set email alerts
|

Republished: Mechanical thrombectomy for repeated cerebral tumor embolism from a thoracic sarcomatoid carcinoma

Abstract: Cerebral embolism originating from intracardiac tumors represents a rare cause of stroke and has been documented in both adult and pediatric populations. We present a patient recently diagnosed with a right pulmonary hilum tumor, invading the pulmonary veins and the left atrium. Two consecutive episodes of large cerebral vessel occlusion in separate vascular territories occurred in the same day and were treated by mechanical thrombectomy. Embolic material retrieved on both occasions contained tumor fragments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The thrombi retrieved from the four patients with cerebral embolization due to extracardiac tumors shown in Table 1 were white and hard, and had different morphological characteristics from usual thormbi. 1 , 10 , 11 , 14) However, the appearance and elasticity of the embolus in our patient did not differ from those of usual thrombi. We initially considered the etiology of infarction to be cardiogenic cerebral embolism because of the history of paroxysmal atrial fibrillation, but eventually diagnosed as tumor embolism based on pathological findings.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The thrombi retrieved from the four patients with cerebral embolization due to extracardiac tumors shown in Table 1 were white and hard, and had different morphological characteristics from usual thormbi. 1 , 10 , 11 , 14) However, the appearance and elasticity of the embolus in our patient did not differ from those of usual thrombi. We initially considered the etiology of infarction to be cardiogenic cerebral embolism because of the history of paroxysmal atrial fibrillation, but eventually diagnosed as tumor embolism based on pathological findings.…”
Section: Discussioncontrasting
confidence: 51%
“…Of the 15 reported cases of tumor embolism, 4 had extracardiac tumor. Of the four cases of extracardiac tumor, three had lung cancer infiltrating the pulmonary vein and left atrium, 10 , 11 , 14) and one had phyllodes tumor of the breast with pulmonary metastasis invading the pulmonary vein. 1) …”
Section: Discussionmentioning
confidence: 99%
“…She was noted to have large masses in both atria which were thought to be the nidus for tumor embolus. While this case and others [14, 15] demonstrate successful endovascular mechanical thrombectomy for tumor emboli in adults, mechanical thrombectomy in the pediatric population presents additional technical challenges given the smaller size of the patients and their vasculature, which can significantly limit device selection. In one of the larger retrospective studies of thrombectomies in children, Sporn et al [6] showed that younger children had poorer outcomes in their group, which could be partially due to the smaller vessel size and more difficult access in those patients.…”
Section: Discussionmentioning
confidence: 88%
“…Cerebral artery tumor embolism induces acute neurological disorder; however, it is rarely diagnosed because of its low incidence and necessity of histological confirmation [ 12 , 13 ]. There is one published review of histological diagnoses of 14 cases which had undergone endovascular mechanical embolectomy for tumors causing acute cerebral ischemic stroke [ 14 ].…”
Section: Discussionmentioning
confidence: 99%